Manipulation of flowering period and shoot multiplication in Clivia miniata (Lindley) Regel - Robbertse, P.J. (Petrus Johannes), 1932- (University of Pretoria, 2013)
Dissertation (MSc (Ornamental Horticulture))--University of Pretoria, 2006.